Sustainable supply chain governance practices in highly regulated market environment: Example from the renewables industry - Ottela, Anette (My University, 2022)
There is necessity for significant reductions of greenhouse gas (GHG) emissions in the transport sector to reach the climate targets of the Paris Agreement. To reduce dependence on the petroleum-based fuels, waste and residue-based biofuels are viewed as promising alternative transportation fuels. This research was conducted as a qualitative single case study within a case company, which is world ́s leading waste and residue based renewable diesel producer. To ensure the sustainability of biofuels, European Union (EU) has established a sustainability criterion for biofuels and bioenergy through the Renewable Energy Directive (RED II). The RED II is the main tool for EU to regulate the case company directly. The case company faces institutional pressures also from other stakeholder groups, such as customers, competitors, national governments, investors, NGOs, and multinational stakeholder initiatives. This research examines what are the institutional pressures affecting the case company, and how the case company is using it ́s sustainable supply chain governance practices in this highly regulated environment. This thesis will discuss the topic through institutional theory as a theoretical lens and supply chain governance as a framework. The importance of supply chain governance in the context of biofuels has been recognised among researchers. There is also research gap in the institutional theory in the context of supply chain governance literature, which creates a need for further research. The findings of this thesis offer new theoretical implications filling the identified research gap on the institutional theory-based research within supply chain management. The case company faces mainly coercive and normative pressures for sustainability. The case company uses direct, indirect, formal, and informal governance mechanisms to ensure sustainability in, of and through supply chains. The theoretical findings of this thesis highlight the role of voluntary assessment initiatives. Although the EU and national level authorities have a prominent role in regulating biofuel supply chains, also the private regulation is needed. At a minimum, companies must comply with mandatory regulations set by the EU. Also, the need for harmonization of biofuel regulations is recognized. As the renewables industry grows, the need for certified products will increase, which requires more collaboration between firms as well as multinational stakeholder initiatives.

Liikennesektorin kasvihuonekaasupäästöjä on vähennettävä merkittävästi Pariisin sopimuksen ilmastotavoitteiden saavuttamiseksi. Jäte- ja jäännösraaka-ainepohjaisia polttoaineita pidetään lupaavina vaihtoehtoisina liikennepolttoaineina fossiilisille polttoaineille.Tämä tutkimus tehtiin laadullisena yksittäistapaustutkimuksena case-yrityksessä, joka on maailman johtava jäte- ja jäännösraaka-ainepohjaisen uusiutuvan dieselin tuottaja. Biopolttoaineiden kestävyyden varmistamiseksi EU on asettanut uusiutuvan energian direktiivillä (RED II) biopolttoaineille ja bioenergialle kestävyyskriteerit. RED II on EU:n tärkein työkalu tapausyrityksen suoraan sääntelemiseen. Tapausyritykseen kohdistuu institutionaalisia paineita myös muiden sidosryhmien, kuten asiakkaiden, kilpailijoiden, hallitusten, sijoittajien, kansalaisjärjestöjen ja monikansallisten sidosryhmäaloitteiden taholta. Tässä tutkimuksessa tarkastellaan, mitkä ovat tapausyritykseen vaikuttavat institutionaaliset paineet ja kuinka tapausyritys käyttää kestävän toimitusketjun hallintakäytäntöjään tässä erittäin säännellyssä ympäristössä. Tässä Pro-gradussa käsitellään aihetta institutionaalisen teorian kautta toimitusketjujen hallinta viitekehyksenä. Toimitusketjujen hallinnan merkitys biopolttoaineiden yhteydessä on tunnustettu tutkijoiden keskuudessa. Institutionaalisen teorian tutkimusvaje toimitusketjujen johtamisen tutkimuksessa luo tarvetta lisätutkimukselle. Tämän Pro-gradun tulokset tarjoavat uusia teoreettisia implikaatioita, jotka täyttävät tunnistetun aukon toimitusketjun hallinnan institutionaalisessa teoriapohjaisessa tutkimuksessa. Tapausyritys kohtaa pääasiassa pakottavia sekä normatiivisia kestävyyden paineita. Tapausyritys käyttää suoria, epäsuoria, muodollisia sekä epävirallisia hallintomekanismeja varmistaakseen kestävyyden toimitusketjussaan. Tämän tutkimuksen teoreettiset havainnot korostavat vapaaehtoisten arviointialoitteiden roolia. Vaikka EU:n ja kansallisen tason viranomaisilla on merkittävä rooli biopolttoaineiden toimitusketjujen säätelyssä, tarvitaan myös yksityistä sääntelyä. Yritysten tulee noudattaa vähintään EU:n pakottavia määräyksiä. Myös biopolttoainemääräysten harmonisoinnin tarve tunnistetaan. Uusiutuvan teollisuuden kasvaessa sertifioitujen tuotteiden tarve kasvaa, mikä edellyttää entistä enemmän yritysten välistä yhteistyötä sekä monikansallisia sidosryhmien aloitteita.
Keywords: kestävä toimitusketjun hallinta, toimitusketjun hallinta, biopolttoaineteollisuus, institutionaaliset paineet